2022
DOI: 10.1371/journal.pone.0265307
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in a differentiated HIV service delivery intervention in Tanzania: A mixed-methods study

Abstract: Background Differentiated service delivery (DSD) offers benefits to people living with HIV (improved access, peer support), and the health system (clinic decongestion, efficient service delivery). ART clubs, 15–30 clients who usually meet within the community, are one of the most common DSD options. However, evidence about the quality of care (QoC) delivered in ART clubs is still limited. Materials and methods We conducted a concurrent triangulation mixed-methods study as part of the Test & Treat project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…RoC in both locations were concerned with privacy and the potential for stigma, making a deliberate choice to remain in their care location to avoid HIV-related stigma. While DSD is scaling up, frequently to community settings, previous studies suggest fear of unintended disclosure as a barrier to uptake of community-based DSD models [5,6,8,11,12,26]. In our study, some clinic-based RoC compromised travel and time concerns to receive care at LT, rather than in the community, to avoid being seen receiving HIV-related services.…”
Section: Discussionmentioning
confidence: 69%
“…RoC in both locations were concerned with privacy and the potential for stigma, making a deliberate choice to remain in their care location to avoid HIV-related stigma. While DSD is scaling up, frequently to community settings, previous studies suggest fear of unintended disclosure as a barrier to uptake of community-based DSD models [5,6,8,11,12,26]. In our study, some clinic-based RoC compromised travel and time concerns to receive care at LT, rather than in the community, to avoid being seen receiving HIV-related services.…”
Section: Discussionmentioning
confidence: 69%
“…Fear of being recognised when participating in CHW‐DCM has been reported previously [22]. Recent qualitative data in the same region showed the opposite for some people: they preferred the anonymity of CHW‐DCM versus crowded facility [20].…”
Section: Discussionmentioning
confidence: 71%
“…The difference in stability in care seemed to be due to poorer adherence among clients in SoC; despite this, the proportion virally suppressed did not differ significantly, however, this may lag behind poor adherence. An important contributing factor to better treatment stability could be more individualised caregiving as reported in a study assessing quality of care in the same study population [20]. The authors of this study reported clients attending CHW‐DCM spend almost half the time as those attending SoC, having better access to health providers (CHW), and receiving adequate reminders for appointments and explanations on the benefits of regular use of ART [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations